Whole Pelvic Radiotherapy With Stereotactic Body Radiotherapy Boost vs. Conventionally Fractionated Radiotherapy for Patients With High or Very High-Risk Prostate Cancer - Wang, Shih-Chang; Ting, Wei-Chen; Chang, Yun-Ching; Yang, Ching-Chieh; Lin, Li-Ching; Ho, Hsiu-Wen; Chu, Shou-Sheng; Lin, Yu-Wei (Frontiers in Oncology, 2020)
Background: Whole pelvic radiotherapy (WPRT) with stereotactic body radiotherapy (SBRT) boost has been shown to be effective in patients with high-risk prostate cancer (PC). However, no study has directly compared the efficacy of WPRT with SBRT boost with that of conventionally fractionated radiotherapy (CFRT). We compared the clinical outcomes between CFRT and WPRT with SBRT boost in patients with high or very high-risk PC (National Comprehensive Cancer Network definition). Methods: In total, 132 patients treated with CFRT and 121 patients treated with WPRT followed by SBRT boost were retrospectively analyzed. For the CFRT group, the prescribed dose range was 74–79.2 Gray (Gy) administered at 1.8–2 Gy per fraction. For WPRT with SBRT boost, the prescribed doses were 45 Gy administered in 25 fractions to the whole pelvis followed by 21 Gy boost (3 fractions of 7 Gy each) to prostate and seminal vesicles. The overall survival (OS) and biochemical failure (Phoenix definition) free survival (bFFS) were assessed by using the Kaplan–Meier method or the Cox proportional hazards regression model. The gastrointestinal (GI) and genitourinary (GU) tract toxicity were assessed using the National Cancer Institute Common Terminology Criteria for Adverse Events (CTCAE) v3.0. Results: The estimated 4-year overall survival in the CFRT and WPRT with SBRT boost groups was 91.6% and 97.7%, respectively (P = 0.18). The estimated 4-year biochemical failure-free survival in the CFRT and WPRT with SBRT boost groups was 89.1% and 93.9%, respectively (P = 0.41). No acute grade 3 or higher GI and GU toxicity was observed in both groups. Late grade 3 GI and GU toxicity occurred in 2.3% and 2.3% in the CFRT group, and in 1.7% and 0.8% in the WPRT with SBRT boost group, respectively. There was no significant between-group difference with respect to acute or late toxicity. Conclusions: In patients with high or very high-risk localized PC, compared with CFRT, WPRT with SBRT boost resulted in similar biochemical-free and overall survival rate with minimal toxicity. WPRT with SBRT boost is a feasible option for patients with high or very high-risk PC.